2018
DOI: 10.1051/0004-6361/201731671
|View full text |Cite
|
Sign up to set email alerts
|

An outflow in the Seyfert ESO 362-G18 revealed by Gemini-GMOS/IFU observations

Abstract: We present two-dimensional stellar and gaseous kinematics of the inner 0.7 × 1.2 kpc 2 of the Seyfert 1.5 galaxy ESO 362-G18, derived from optical (4092-7338 Å) spectra obtained with the GMOS integral field spectrograph on the Gemini South telescope at a spatial resolution of ≈170 pc and spectral resolution of 36 km s −1 . ESO 362-G18 is a strongly perturbed galaxy of morphological type Sa or S0/a, with a minor merger approaching along the NE direction. Previous studies have shown that the [O iii] emission sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 83 publications
0
22
0
Order By: Relevance
“…Given the uncertainties, we only conclude that the mass of central SMBH is of the order of several 10 7 M , which is a typical mass for SMBHs in nearby galaxies (e.g. Greene & Ho 2005;Busch et al 2017;Humire et al 2018;Slater et al 2019;Fazeli et al 2019).…”
Section: Smbh Massmentioning
confidence: 77%
“…Given the uncertainties, we only conclude that the mass of central SMBH is of the order of several 10 7 M , which is a typical mass for SMBHs in nearby galaxies (e.g. Greene & Ho 2005;Busch et al 2017;Humire et al 2018;Slater et al 2019;Fazeli et al 2019).…”
Section: Smbh Massmentioning
confidence: 77%
“…ESO 362-G18 is classed as a non-detection as only the Ar xviii feature is a prominent variability feature and the relatively high overall significance is merely due to inaccurate spline fitting. Humire et al (2018) does report on 100-250 km s −1 outflowing gas within the AGN ionization cone, however, these are much below the 0.033c velocity limit to be considered UFOs.…”
Section: A3 Comments On Ufos With No Evidencementioning
confidence: 90%
“…In order to better understand the extent, geometry, kinematics and energetics of the narrow-line region (NLR) on ≤100-pc scales in a well-defined sample of nearby AGNs, we have been pursuing highresolution integral field unit (IFU) observations of (∼30) Seyfert galaxies from the Hubble Space Telescope (HST) [O III] Snapshot Survey of Schmitt et al (2003) selected to (a) have NLRs that extend beyond ∼1 arcsec from the nucleus, and (b) cover the full range (39 ≤ log (L[O III]) ≤ 42 erg s −1 ) of AGN luminosities of the sample. Results on individual or subsets of galaxies can be found in Schnorr-Müller et al (2014a,b), Riffel, Storchi-Bergmann & Riffel (2015), Lena et al (2016), Finlez et al (2018), Humire et al (2018), Freitas et al (2018), Slater et al (2019), Muñoz-Vergara et al (2019) and Ramakrishnan et al (2019), and overall results of the study will be published on completion of the sample. As part of this study, we observed ESO 153-G20 with the IFU of the Gemini multi-object spectrograph (GMOS-IFU).…”
Section: Introductionmentioning
confidence: 99%